Application of Laparoscopic Radical Resection for Type III and IV Hilar Cholangiocarcinoma Treatment - Sulai Liu; Xinyu Liu; Xuepeng Li; Ou Li; Weimin Yi; Junaid Khan; Pingzhou Yang; Chao Guo; Chuang Peng; Bo Jiang (Gastroenterology Research and Practice)
Background. This study is aimed at investigating the feasibility and safety of the laparoscopic radical resection for treating type III and IV hilar cholangiocarcinoma (III/IV Hilar C). Methods. Six patients with III/IV Hilar C were enrolled in our hospital. All patients underwent total laparoscopic surgery, including basic surgery (laparoscopic gallbladder, hilar bile duct, and common bile duct resection and hepatoduodenal ligament lymph node dissection) combined with left hepatic and caudate lobe resection/portal resection. The tumor size, operation time, intraoperative blood loss, and postoperative complications were observed. The follow-up of the patients after discharge was recorded. Results. Surgery was successfully completed in 6 patients. We found that the tumor size of 6 patients ranged from 1.5 to 3.6 cm, with 4 lymph nodes. The operation time was 540-660 minutes, and the blood loss was 300-500 ml. One patient developed bile leakage after surgery, healed within 2 weeks after drainage. The postoperative hospital stay was 16 (13-24) days. There were 4 cases of negative bile duct margin tumor, 1 case was positive, and 1 case was not reported. All 6 patients were discharged smoothly without perioperative death. Regular examinations were conducted every 3 months after discharge, and the median duration was 7 months. Only 1 patient had a marginal dysplasia, and 5 patients had no obvious signs of recurrence. Conclusions. Application of laparoscopic radical resection for III/IV Hilar C is safe and feasible and has good short-term efficacy with adequate preoperative evaluation, appropriate case selection, and precise operative strategy.